The Impacts of Mobile Platform Openness on Application Developers' Intention to Continuously Use a Platform: From an Ecosystem Perspective - Goya Choia; Changi Nam; Seongcheol Kim (International Telecommunications Society (ITS), 2017)
With the development of information and communication technologies and the emergence of the Internet of things, the open-platform strategy has come into the spotlight. Opening a platform allows external firms or individuals to enter the platform ecosystem without any restriction. Even though a platform connects diverse products and services, previous studies have focused on the bilateral relationship between a platform and a single group of product or service. This research investigates platform openness to multiple groups of products and services in an ecosystem simultaneously; research has especially focused on how the openness of the Android platform to both applications and devices influences application developers' intention to continuously participate. First, openness to applications influences not only the participation intention of application developers directly but also the user base of the platform and competition among developers. An increased user base leads to an enhanced participation intention of developers through indirect network effects, while intense competition does not have a significant effect on intention. Second, openness to devices also influences the participation intention of application developers indirectly. Openness to devices contributes to enlargement of the user base which positively influences the intention of application developers. Openness to device also incurs coordination costs between applications and devices, which have a partially negative effect on the participation of application developers. In this paper, we propose a comprehensive model that explains the impact of platform openness on application developers in order to offer a deeper understanding of the mechanisms of platform openness.
Keywords: 330; Platform openness; Platform ecosystem; Android; Expectation-confirmation model